2009
DOI: 10.3168/jds.2008-1382
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of Streptococcus uberis-induced mastitis reveals fundamental differences between immune gene expression in the mammary gland and in a primary cell culture model

Abstract: Streptococcus uberis is a prevalent causative organism of mastitis and resides naturally in the environment of the dairy cow making prevention of the disease difficult. A bovine cDNA microarray comprising approximately 22,000 expressed sequence tags was used to evaluate the transcriptional changes that occur in the mammary gland after the onset of clinical Strep. uberis mastitis. Five lactating Friesian heifers were intramammary infused in an uninfected quarter with approximately 1,000 to 1,500 cfu of a wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 48 publications
9
123
6
Order By: Relevance
“…However, two important innate immune genes, TNFa and CD14, were identified as differentially expressed by the RT-qPCR, but not on the microarray. Swanson et al (2009) infected heifers with Streptococcus uberis and measured the transcriptional changes in the mammary tissue on a DNA microarray. Of the regulated genes, they validated 11 innate immune genes with RT-qPCR.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two important innate immune genes, TNFa and CD14, were identified as differentially expressed by the RT-qPCR, but not on the microarray. Swanson et al (2009) infected heifers with Streptococcus uberis and measured the transcriptional changes in the mammary tissue on a DNA microarray. Of the regulated genes, they validated 11 innate immune genes with RT-qPCR.…”
Section: General Considerationsmentioning
confidence: 99%
“…Possibly, the dose of inoculation was insufficient. It could have been too low, taking into account that there is a dose-dependent immune response of pbMEC to lipopolysaccharide (LPS) and S. aureus (Wellnitz and Kerr, 2004) and a study by Swanson et al (2009) with pbMEC from tissue showed an upregulation in four of nine measured immune genes to S. aureus with a much higher MOI of 1000. Another possibility is that we missed the proper time frame of the immune response: one study showed an early immune response of MECs to S. aureus that decreased to resting levels after 8 to 16 h (Strandberg et al, 2005).…”
Section: Pathogen Differencesmentioning
confidence: 99%
“…Following digestion, DMEM/F-12 (Gibco-BRL, Invitrogen Life Technologies, Carlsbad, CA, USA) containing 0.04 mg/ml DNase (Sigma-Aldrich) was added and the mixture was incubated at 37˚C for 8-10 min, as described in detail previously (8)(9)(10). The resulting single cell suspension seeded into a 24-well cell culture plate pre-coated coated with polylysine and then cultured under standard conditions (37˚C, 5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study shows the importance of developing models with polarised mammary epithelial cells and that BME-UV1 may be a good model for studying, for example, developmental processes of the bovine mammary gland in vitro. Primary cells of the bovine mammary gland have also been used as models including both organoids, explants and epithelial cells for studies of effects of growth factors, steroids, lactoferrin, retinoids, cytokines, biogenic amines, mammary extracts, and endpoint parameters such as mitogenic activity and gene expression have been measured Bauman, 1999 andWeber et al, 1999;Akers et al, 2000;Ellis et al, 2000;Purup et al, 2000 andWeng et al, 2005;Thorn et al, 2006 andErnens et al, 2007;Fusi et al, 2008;Swanson et al, 2009;Wang and Baumrucker, 2010). Both primary mammary cells and cell lines of human and rodent origin have been used to study effects of milk-derived bioactives such as CLA and phytoestrogens.…”
Section: Cell-based Models Of the Mammary Glandmentioning
confidence: 99%